Stroke in pediatric: a review - Nugroho Danu; Melinda; Astarini Hidayah (Medical Faculty of Brawijaya University, Indonesia, 2022)
Stroke in children was defined as the clinical and radiological manifestation of stroke, with radiological evidence of cerebral infarction or hemorrhage. Pediatric stroke can be divided into ischemic and hemorrhagic stroke. The etiology is very different, and diagnostic procedures are often more in-depth to look for etiology. Stroke is classically characterized by acute focal neurologic deficits such as hemiplegia, speech, or gait disturbances; presentation is highly dependent on the child’s age and may be non-specific. When acute focal neurologic deficits are found in childhood, one should think about stroke until proven otherwise. There is no standard therapy based on a systematic review of a randomized clinical trial. Therapeutic recommendations are the consensus of experts, extrapolated from the recommendations for stroke therapy for the adult population. Understanding stroke in children is complicated because it has broad differential diagnosis, and complications that occur. Therefore, early recognition of childhood stroke by pediatricians is very important with the implementation of targeted and neuroprotective therapies.